Utilizing Advocacy Journalism for Rural Development in Taraba State - Asicus, Samuel; MERCY TARTSEA–ANSHASE; DESMOND OKOCHA ONYEMECHI (PT Pro Panoramic Solution, 2025)
Development in most developing countries has been uneven and lopsided owing to several reasons stemming from horizontal flow of development communication and urban-centred nature of the mass media, high level of illiteracy, non-involvement/participation of other segments of the society, particularly the rural areas, among other factors. This study, therefore, examines the utilisation of advocacy journalism for the promotion of rural development in Taraba State. Democratic participant media theory was used as the theoretical underpinning for the study. The study adopts an in-depth interview as a methodology where data were collected from journalists in public and private media outfits in Taraba State. The findings of the study show that although journalists in Taraba state know about advocacy journalism, the majority do not practice advocacy journalism owing to operational difficulties, poor funding, and a lack of proper orientation on advocacy, among others. Among other things, the study recommends the need for the incorporation of advocacy journalism into the curriculum and training of journalists in Nigeria at all levels. The study also recommends that government and private media owners should improve the funding and remuneration of journalists, as well as help them surmount operational difficulties to carry out their responsibility of advocacy effectively.